Tocopherols composition of Portuguese wild mushrooms with antioxidant capacity - Heleno, Sandrina A. (2010)
The antioxidant composition and properties of 18 Portuguese wild mushrooms (Clitocybe alexandri, Cortinarius glaucopus, Fistulina hepatica, Hydnum repandum, Hygrophoropsis aurantiaca, Hypholoma capnoides, Laccaria amethystina, Laccaria laccata, Lactarius aurantiacus, Lactarius salmonicolor, Lepista inversa, Lepista sordida, Mycena rosea, Russula delica, Russula vesca, Suillus collinitus, Suillus mediterraneensis, Tricholoma sulphureum) were evaluated, in order to contribute to the overall characterisation of these products. Their radical-scavenging capacity, reducing power and inhibition of lipid peroxidation measured in liposome solutions was fully studied. Furthermore, the tocopherols composition was determined by HPLC-fluorescence. The analysed mushrooms contain powerful antioxidants such as phenols (0.51– 7.90 mg/g) and tocopherols (0.02–8.04 lg/g). b-Tocopherol was the vitamer detected in higher amounts, while d-tocopherol was not detected in the majority of the samples. All the species proved to have antioxidant activity being more significant for H. aurantiaca (EC50 values lower than 1.35 mg/ml) due to the contribution of antioxidants such as phenols (7.90 mg/g) and tocopherols (0.02–1.94 lg/g). The ongoing research states the nutraceutical potential of all these unique species, making the information available for a better management and conservation of mushrooms and related habitats.